2009
DOI: 10.1073/pnas.0802674106
|View full text |Cite
|
Sign up to set email alerts
|

The conserved NAD(H)-dependent corepressor CTBP-1 regulates Caenorhabditis elegans life span

Abstract: CtBP (C-terminal binding protein) is an evolutionarily conserved NAD(H)-dependent transcriptional corepressor, whose activity has been shown to be regulated by the NAD/NADH ratio. Although recent studies have provided significant new insights into mechanisms by which CtBP regulates transcription, the biological function of CtBP remains incompletely understood. Here, we report that genetic inactivation of the Caenorhabditis elegans homolog, ctbp-1, results in life span extension, which is suppressed by reintrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 56 publications
(62 reference statements)
2
61
1
Order By: Relevance
“…Worms possessing a mutant form of ctbp-1 display an extension of life span, which can be suppressed by the reintroduction of ctbp-1. The function of ctbp-1 in life span control in C. elegans is dependent on its NAD ϩ / NADH binding activity (39). CTBP proteins can bind to NAD ϩ /NADH dinucleotides at concentrations comparable with those present within the cell (17).…”
Section: Discussionmentioning
confidence: 99%
“…Worms possessing a mutant form of ctbp-1 display an extension of life span, which can be suppressed by the reintroduction of ctbp-1. The function of ctbp-1 in life span control in C. elegans is dependent on its NAD ϩ / NADH binding activity (39). CTBP proteins can bind to NAD ϩ /NADH dinucleotides at concentrations comparable with those present within the cell (17).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, both studies identify age-dependent alterations in the expression of select modifiers of chromatin state (Rossi et al, 2005;Chambers et al, 2007). Interestingly, chromatin modifiers have recently been found to control longevity in model organisms such as yeast, flies and worms Chen et al, 2009;Dang et al, 2009;Greer et al, 2010;Siebold et al, 2010). In addition, chromatin modifiers have been implicated in the control of a number of cellular processes that may contribute to longevity, including DNA damage repair, telomere maintenance and cellular metabolism (Vidanes et al, 2005;Longo and Kennedy, 2006;Blasco, 2007).…”
Section: Chromatin Modifiers In Aging Stem Cellsmentioning
confidence: 99%
“…Interestingly, a number of recent studies have reported that genes promoting lipolysis or fatty acid desaturation also promote longevity (11,19,33,55). Potentially, this could reflect altered energy metabolism, or changes to lipid composition, membrane fluidity, and signaling pathways (10,11).…”
Section: Age Changes In Yolk and Lipid Dropletsmentioning
confidence: 99%
“…Potentially, this could reflect altered energy metabolism, or changes to lipid composition, membrane fluidity, and signaling pathways (10,11). A further possibility is that they retard the accumulation of pathogenic forms of lipid (e.g., lipotoxic inclusions) (1).…”
Section: Age Changes In Yolk and Lipid Dropletsmentioning
confidence: 99%